HUBUNGAN PENGETAHUAN ORANG TUA DENGAN PERSEPSI TENTANG KEKERASAN PADA ANAK - Amyur Murni; Salmah Salmah (Jurnal Ilmu dan Teknologi Kesehatan, 2013)
Background: Law no. 23/2002 on Child Protection section 13 violence against children is discrimination, exploitation, physical and sexual abuse, neglect, ruelty,violence, and persecution, injustice, and other abuses. Objective: to know the parents' perceptions of the form of child abuse and factors - factors that influence in the region Pedongkelan kayu putih Village East Jakarta District Pulogadung period in 2012. Methods: This type of research is analitic, cross-sectional study design. Data were collected using a questionnaire Results: There is a significant relationship between parental perception of violence in children with parental knowledge level (P value 0.000), economic level (P value 0.007) and there was no significant relationship between parental perception of violence on children aged parents (P value 0.322), education level (P value 0.882), number of children (P value 0.882), Parent Child Interaction (P value 0.401). Conclusion: The need for increased knowledge about child abuse so as to improve the perception of parents and the need for collaboration across sectors and programs to drive the family's economic status and reduce the burden on parents.